Islam and Humanity: Commodification of Aid for Rohingya in Aceh - Lindra Darnela (Al-Jami'ah: Journal of Islamic Studies, 2021)
This study examines how Rohingya refugees in Aceh in 2015-2016 received assistance and the role of Islamic philanthropic institutions in providing aid. The paper shows that through the media, Islamic philanthropic institutions have successfully advocated for Rohingya rights and raised the issue as a religious issue so that they have collected large donations. Also, this paper finds a discrepancy between the information conveyed by the media and the reality in the field, showing significant efforts in the commodification of humanitarian aid and abuse of religion.[Artikel ini membahas bagaimana pengungsi Rohingya di Aceh periode 2015-2016 mendapatkan bantuan dan peran dari lembaga filantropi Islam dalam penyediaan bantuan tersebut. Artikel ini menjelaskan bahwa lembaga filantrofi Islam berhasil mengadvokasi hak Rohingya melalui media dan mengkaitkan dalam isu agama sehingga mendapatkan donasi yang berlipat. Selain itu dalam artikel ini juga menunjukkan ketidaksesuaian antara informasi di media dengan kenyataan di lapangan, bahkan terdapat indikasi komodifikasi bantuan kemanusiaan dan penyalahgunaan agama.]